IMPLEMENTATION OF BORDER CONTROL MANAGEMENT SYSTEM FROM THE SECURITY SIDE (SELECTIVE POLICY) IN IMMIGRATION EXAMINATIONS OF SOEKARNO-HATTA INTERNATIONAL AIRPORT - Revinka Dyah Fatcahya (Polteknik Imigrasi, 2020)
This journal discusses the implementation of the Border Control Management (BCM) system which is integrated with the Enhanced Cekal System (ECS), the Interpol I-24/7 system and also with the repository servers such as residence permits and DPRI systems in terms of security in this case based on the principle of selective policy. This form of research uses qualitative research with descriptive methods. Based on the research conducted, in the BCM system there is an Immigration Data Exchange as a regulator of integration between applications. The application of an integrated system in BCM makes the results of immigration checks at the time of scanning the passport showing the status of a ban, visa and residence permit, the last crossing, the status of Interpol, checking the transportation means, and checking other passports. However, the system is still often partially connected so that the Class I Special TPI Soekarno-Hatta Immigration Office must make various efforts such as having a Special IT team and making innovations to make immigration checks at TPI easier and more effective and in accordance with the principle of selective policies implemented by Indonesia.